Integration of Circular Economy for Sustainable Business Performance: Bibliometric and Content Analysis - Franconnie, Kalika Dianti (JURNAL ONLINE INSAN AKUNTAN, 2024)
Expansion of middle-class population and the scarcity of resources urge circular economy to be implemented into business processes. This study aims to gain understanding into the circular economy, including its trends, predominant research themes, and the evolution of knowledge on the topic. A total of 675 documents from 1996 to June 16, 2023 from Scopus analyzed by bibliometric to examine related sources, authors, productivity, citations, to explore research trends and themes, including analysis on the top 10 most influential articles. This study finds that circularity not only fosters environmental sustainability but also economic advantages such as cost savings, the development of new revenue streams, enhanced risk management, increased job market and innovation. This concept has emerged as a niche term of significant interest among academics, policymakers, and companies. This study provides recommendations for future research and provide support for enterprises in incorporating circularity to enhance their sustainable business performance .